Sometidos al Cuzco y aliados de España. Grupos étnicos andinos ante la Conquista española - Bravo Guerreira, Mª Concepción (Revista Española de Antropología Americana, 2003)
The collaboration of some ethnic groups with Francisco Pizarro’s army, in the campaigns of the conquest of Peru, it is documented in the testimonies of the first chroniclers and of the early documentation of the colonial period. This paper brings together those testimonies that make reference to the support given by Cañaris and Chachapoyas of the northern region of the old Tahuantinsuyu.